Epidemiology of anemia in patients with chronic kidney disease of stages 3-5D: a cross-sectional study in Hengyang,South of Hunan province,China - HE Zhang-xiu; LUO Lei; XIE Huan; ZHAO Sai-li (Linchuang shenzangbing zazhi)
Objective To determine the prevalence of anemia in subjects with chronic kidney disease( CKD) of stages 3 ～ 5,reveal the characteristics of anemia in those patients,and provide data for improving this situation. Methods This was an epidemiological,cross-sectional,single-center study under routine clinical practice conditions. Data of 1 619 CKD 3 ～ 5 patients admitted to the First Affiliated Hospital of South University or in the Hemodialysis Center from February 2012 to June 2018 were used to understand the prevalence of anemia in those patients( stage 3: n = 92; stage 4: n = 301; stage5: n = 989; stage 5 D: n = 237). Results The mean hemoglobin( Hb) level in patients with CKD 3 was( 105. 4 ± 23. 1) g/L,compared to( 88. 4 ± 20. 8) g/L in patients with CKD 4,to( 76. 3 ± 18. 6) g/L with CKD 5 ND( CKD 5 not given dialysis),and to( 88. 0 ± 20. 1) g/L with CKD 5 D( CKD 5 given dialysis). There was statistically significant difference among the groups( P < 0. 01). The overall prevalence of anemia was 72. 83%,94. 68%,97. 77% and 91. 56% in patients with CKD 3,CKD 4,CKD 5 ND and CKD 5 HD,respectively. The prevalence of mild anemia [90 g/L ≤ Hb < 120 g/L( male)/110 g/L( female) ]was 51. 09%( CKD 3),45. 51%( CKD 4),19. 92%( CKD 5) and 36.71%( CKD 5 D) respectively. The prevalence of moderate anemia [60 g/L≤Hb < 90 g/L] was 20.65%( CKD 3),40. 53%( CKD 4),59. 35%( CKD 5) and 44. 72%( CKD 5 D) respectively. According to the standard of anemia in China,the patients with normocytic norchromia and normocytic hypochromia anemia accounted for 64. 65% and 18. 55% separately. The linear regression showed that Hb( g/L) = 66. 81 + 0. 96 × eG FR( R = 0. 45,F = 351. 00,P < 0. 01). Conclusions We found that the prevalence of anemia was increased with the raised prevalence of CKD 3 ～ 5. Normocytic and normochromic anemia is the most common form in patients with CKD 3 ～ 5 D,in accordance with its pathogeneses. In patients with CKD 3 ～ 5,mean Hb level was decreased as eG FR was linearly decreased.